Draft genome of an extremely drug-resistant st551 Staphylococcus pseudintermedius from an Italian dog with otitis externa. (June 2021) - Vitali, Luca A.; Beghelli, Daniela; Balducci, Massimo; Petrelli, Dezemona
Highlights: A MDR Staphylococcus pseudintermedius strain CAM1 was characterized by WGS. S. pseudintermedius CAM1 belonged to st551. The strain also harboured tet K, which is extremely rare in this species. Abstract: Objectives: To determine the draft genome sequence and analyse the genetic features of a Staphylococcus pseudintermedius clinical isolate according to the main typing schemes available, with a special focus on antibiotic resistance. Methods: The strain was isolated from a case of otitis externa in a dog. Its identity and pattern of antibiotic susceptibility were determined using an automated system. The genome was sequenced using an Illumina platform. MLST, SCCmec typing, resistome, and mobile genetic elements were derived by comparative analysis using available specific databases. Results: S . pseudintermedius CAM1 isolate has a chromosome size of 2 652 610 bp. It showed a wide pattern of phenotypic resistance, comprising beta-lactams, macrolides and lincosamides, aminoglycosides, fluoroquinolones, tetracyclines, and trimethoprim-sulfamethoxazole. The genetic determinants of the underlying mechanisms were all found by in silico analysis of the genome. The mec A gene for methicillin resistance was harboured by the Vc type of the SCCmec. MLST of the strain was st551. Conclusion: By comparison with the MLST database of S. pseudintermedius and data from published molecular epidemiology studies, CAM1 is the first st551 strain recorded in Italy and, in the context of an already extremely wide antibiotic resistance pattern, it harbours also the tet K gene, the prevalence of which is rare in MDR S. pseudintermedius .